GIS-material for the archaeological project: A long-standing settlement in Veta - Excavation preceding planned building plots in the western outskirts of Mantorp - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a new residential area, the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a final excavation within the property Veta 5:5, Veta parish, Mantorp, Mjölby municipality, Östergötland County. A survey and preliminary investigation were conducted in 2004, discovering extensive settlement remains. The development area was approximately 50 000 m2 big, and the final excavation in 2005 covered about 8700 m2 of it. Three settlement areas were excavated. Within area A, a longhouse from the late Roman Iron Age was found, as well as areas with hearths and pits. The house was unusually complete, compared to the houses normally found in Östergötland. Both the roof-supporting post holes and the post holes of the walls had been preserved. Within area B at least four houses were found; a longhouse and at least two more diffuse buildings from the the Roman Iron Age, and a neolithic longhouse. Nearby this house, just beside the ancient stream bed that crosses the area, 2 kg of bell-beaker pottery ornamented with lines along the body was discovered. It is the largest collection of this kind of pottery found in Östergötland county. Furthermore, a great number of other features were found within area B, such as post holes, hearths, pits, wall trenches, a large packing of fire-cracked stones and two wells. The stone packing was dated to the early Bronze Age while most of the other settlement remains were dated from the centuries around 0 AD to c. 400 AD. The area also contained ancient and very thick agricultural layers, extending down to the stream. The farming in Veta probably started already in the Stone Age and continued into the Roman Iron Age.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the final excavation was to document the archaeological site RAÄ 45 before its removal, in such a way that the information could be studied by archaeologists and laymen alike in the future. The purpose was also to take care of all representative and relevant artefacts found.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet, UV Öst, utförde 2004-2005 arkeologiska undersökningar inom fastigheten Veta 5:5, Veta socken, Mantorp, Mjölby kommun, Östergötland. Undersökningarna föranleddes av att Mjölby kommun planerade för ny villabebyggelse. Utredningsgrävning och förundersökning utfördes 2004 och konstaterade ett omfattande boplatsområde. Det totala exploateringsområdet uppgick till ungefär 50 000 m2 och cirka 8700 m2 banades av vid slutundersökningen som utfördes 2005. Ytterligare något hundratal kvadratmeter undersöktes vid utredningsgrävningen och förundersökningen. Tre boplatsområden undersöktes. Inom område A påträffades ett treskeppigt långhus från yngre romersk järnålder samt aktivitetsytor med härdar och gropar. För Östergötlands del var detta hus ovanligt intakt och hade såväl takbärande stolphål som väggarnas stolphål bevarade. Inom område B påträffades minst fyra hus; ett treskeppigt långhus samt ytterligare ett par något diffusa hus från romersk järnålder. Ett av husen var en mesulakonstruktion från neolitisk stenålder. I husets närhet, intill den forna bäcken som genomkorsar området, hittades också cirka 2 kg trattbägarkeramik med bukstreck från samma period. Detta är det hittills största enskilda materialet av trattbägarkeramik med bukstreck som hittats i Östergötland. Dessutom hittades inom område B ett stort antal övriga lämningar såsom stolphål, härdar, gropar, rännor, ett stort skärvstensflak och två brunnar. Skärvstensflaket kunde konstateras vara från äldre bronsålder men största delen av boplatslämningarna i område B kommer från tiden kring århundradena runt Kristi födelse och fram till omkring 400 e Kr. Dessutom innehöll området mycket tjocka odlingslager ned mot bäcken som kunde konstateras vara mycket gamla. Förmodligen påbörjas odlingen i Veta redan under stenålder och löper ända fram till romersk järnålder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska slutundersökningen var att dokumentera fornlämningen RAÄ 45 före borttagande på ett sådant sätt att informationen från boplatsens alla relevanta delar kan studeras i efterhand för forskarvärlden och en intresserad allmänhet. Syftet var också att ta tillvara alla representativa och relevanta fynd som påträffades.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: En långvarig boplats i Veta - Inför nyplanerade villatomter i Mantorps västra utkant
Keywords: stone age; stenålder; Neolithic; neolitikum; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi